Building health systems capacity in global health graduate programs: reflections from Australian educators - Negin Joel; Martiniuk Alexandra; Morgan Chris; Davies Philip; Zwi Anthony (BMC, 2012)
Abstract There has been increasing focus on the role of health systems in low and middle-income countries. Despite this, very little evidence exists on how best to build health systems program and research capacity in educational programs. The current experiences in building capacity in health systems in five of the most prominent global health programs at Australian universities are outlined. The strengths and weaknesses of various approaches and techniques are provided along with examples of global practice in order to provide a foundation for future discussion and thus improvements in global health systems education.